Kajian Metode Etnografi untuk Penelitian di Bidang Pendidikan - Novia Ananda; Meyniar Albina (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Ethnographic research is one of the qualitative approaches that plays a significant role in understanding social and cultural phenomena within educational environments. This method focuses on direct and in-depth observation of daily activities, social interactions, and communication patterns in an educational community. This article aims to discuss the basic concepts, characteristics, types, advantages, and limitations of ethnographic research in education. In addition, this paper presents several examples of ethnographic studies in the field of education conducted in various regions in Indonesia. This study employs a library research method by collecting relevant literature such as books, journals, and scientific articles. The findings indicate that ethnographic research is not only effective in revealing cultural values within schools but also capable of capturing the interaction patterns and learning experiences of students and educators comprehensively. The results also highlight that a sufficiently long research duration is a crucial requirement for obtaining valid data. This article is expected to serve as a valuable reference for researchers, academics, and education practitioners in understanding and applying ethnographic approaches within educational contexts.